Management Pattern of Chronic venous Disease in Bangladesh (Medicine Today, 2023)
Introduction: Chronic venous disease (CVD) is mostly underdiagnosed diseasewhich may progress to chronic venous insufficiency and venous ulcer thus extensive treatment. CVD may affect negatively into patient’sgood well-beingwhich can create burdens on their life and also healthcare resources. Bangladesh has very minimum awareness on CVD.Materials and Methods: This was a cross-sectional study was carried out in department of vascular surgery of National Institute of Cardiovascular disease. we randomly choose 60 patients with chonic venous disease (CVD) and evaluate their characteristics and prevalence of several types along with the management pattern. Data collection started from May 2021 for next 6 months.Results: The patients of this survey were aged between 24 to 70 years and the Mean±SD age was 43.6±12.2. 78.3% of total study population were male, 33.3% were businessman and 10% were housewife. 66.6% patients were having low socio-economic condition. C2 varicose veins were highly prevalent among the study population ( 35%) & lowest prevalence of C4b lipodermatosclerosis or atrophie blanche (11.7%). Male were predominantly more prevalent to having CVD, 78.33% (n47), (p